2012
DOI: 10.1111/apa.12067
|View full text |Cite
|
Sign up to set email alerts
|

Intensive playing leads to non‐monosymptomatic enuresis in children with low prepulse inhibition

Abstract: While the decrease in PPI when playing was smallest in the group with nmE, overall PPI level was by far the lowest. The findings confirm the aetiology of enuresis through impaired 'sensori-motor gating' in children with nmE and provide a neurophysiologic correlate for wetting while playing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The role of stress and psychological factors in the pathogenesis of ME has been shown in a variety of studies ( 7 , 10 , 11 , 21 ). Recently many studies have identified a delay in neuromotor development in children with ME ( 8 , 9 , 12 , 22 ). These studies assert a maturational deficit of the brainstem as the possible central dysfunction of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The role of stress and psychological factors in the pathogenesis of ME has been shown in a variety of studies ( 7 , 10 , 11 , 21 ). Recently many studies have identified a delay in neuromotor development in children with ME ( 8 , 9 , 12 , 22 ). These studies assert a maturational deficit of the brainstem as the possible central dysfunction of the disorder.…”
Section: Discussionmentioning
confidence: 99%